Attributes of smart bridge monitoring technologies - Teo, Mei Choo (2009)
In the recent past, there have been rapid advances in the development of technologies for the evaluation of bridges. Advanced structural health monitoring has fast become a growing field in which non-intrusive damage detection techniques are integrated into a structure to monitor the complete bridge or individual bridge members. These integrated computer-linked sensors systems could subsequently alert the bridge engineers on the abnormalities inside the bridge structure. These bridge structures could be aptly described with the phrase ‘smart structure’. If properly maintained, it is believed that these smart technologies could extend the useful life of bridges by allowing deterioration to be identified earlier and thereby allowing relatively minor corrective actions to be taken before deterioration grows to a state where major actions are required. In addition, smart bridge technologies allow designers to learn from previous designs to improve the performance of future bridges. While a number of smart bridge monitoring technologies exist, a thorough compilation of these various technologies have not been done in this country. A comprehensive database would allow easy identification and review of smart bridge monitoring technologies and to facilitate the selection of technologies for a specific application. With this database, information on available monitoring technologies could be identified and their applicability could be selected.